The Practice of Management - Drucker, Peter F. 1909-2005 (Jordan Hill Butterworth-Heinemann, 2003)
Providing information about the developments and place of management, this book contributes to the study of business efficiency. It is of interest to the applied economists and sociologists.
Include Bibliogarphy and Index
Keywords: Industrial management -- United States -- Management